DEBATES AND PROGRESEE IN CONTEMPORARY POLITICAL SCIENCE: THE THEORY OF INTERDEPENDENT DECISIONS AND THE SCIENTIFIC STUDY OF POLITICS (Andamios, Revista de Investigación Social, 2009)
Rational Choice Theory, or Theory of Interpersonal Decisions, has a particular importance in contemporary political sciences, which is growing as the theory evolves and involves new methods and perspectives. But very often this theory is ignored from south of the Río Grande. This essay underlines its dynamism and makes a call to assimilate it critically.
Keywords: Progress and programs of political and social sciences; rational choice theory and Interdependent decisions; social sciences and norms of political justice